Soil Transmitted Helminths Infection in Elementary School Students in Highland and Lowland Areas of Gianyar Regency - Nuryanti, Ni Made; Subrata, I Made (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Soil-Transmitted Helminths (STH) Infection is a worm infection which is transmitted through soil. STH is still a public health problems around the world, including Indonesia. The tropical climates of Indonesia is a suitable environment for viability of STH. The prevalence of STH in Bali since 2003-2007 reached 40.94%-92.4%. The altitude of an area may affect the rate of STH infection. The rate of STH infection is higher on population in highland area compared to lowland area. This study aimed to identify risk factors of STH infection in elementary school students in highland and lowland area in Gianyar Regency. This study used cross sectional analytic design and was conducted in 2016. The total samples of this study were 104 students which were consisted of 53 students in highland area and 51 students in lowland area. The samples were collected using cluster random sampling technique. The specimens were examined using Kato-katz method. The results showed that the prevalence of STH infection in elementary school students in highland area (28.31%) was higher than in lowland area (1.96%). In lowland area, the risk factor could not be clearly identified because there was only one student with a positive STH infection. Meanwhile, the identified dominants risk factors which influence STH infection in highland area were habit of washing hands using soap (AOR=24.99), fingernails cleanliness (AOR= 13.19) and parents income (AOR=18.83).